Liberalization and culture in contemporary Israel - Ofengenden, Ari (Lexington Books, 2018)
The book looks at the ways in which Israel's integration into the global economy has affected its main stream culture. Ofengenden uses works of Israeli film, literature, and television, from the past 30 years to conceptualize the changes in Israel's culture.